ANALISIS YURIDIS KEABSAHAN PERBAIKAN DATA FISIK SERTIPIKAT HAK ATAS TANAH MENGGUNAKAN ALAT BAYCLIN - Erycha Finda Rizkyardina; Indrawan; Edi Kurniawan; M.Taufik Razali (JURNAL PURNAMA BERAZAM, 2024)
In providing legal certainty over land, the government, through the Ministry of Agrarian Affairs and Spatial Planning, carries out Land Registration, from this activity, the Rights Holder has strong evidence of the land they own, however, during implementation, many deficiencies were still found, one of which was an error that arose during printing. certificate, therefore existing errors must be corrected. Data correction activities on Land Rights Certificates are reviewed based on applicable regulations from different perspectives. So it will give rise to legal consequences for proving the product certificate issued and criminal sanctions for officials or employees who do so. The formulation of the problem raised in this research is 1) What are the Legal Consequences of Correcting Land Rights Certificate Data Using the Bayclin Tool from the Perspective of Criminal and Civil Law? The aim of this research is to analyze data improvement activities relating to the location, boundaries and area of ​​land parcels and the legal status and rights holders of Land Rights Certificates using the Bayclin tool from a legal perspective. The research was conducted using the Normative Juridical Method. The research results show that improvements to Land Rights Certificate Data have legal consequences if carried out without paying attention to or following existing or established rules.